Entrepreneurial passion development: the interplay between heuristic thinking and pedagogical experience during entrepreneurial learning process - Muhammad Nizam Zainuddin; Dzulkifli Mukhtar; Norhafizah Abu Hasan; Mohd Helmi Ali (Penerbit Universiti Kebangsaan Malaysia, 2019)
The underlying objective of an entrepreneurship education programme (EEP) is to facilitate students to becoming more passionate about entrepreneurship. This is done through the provision of a profound pedagogical learning experience while undergoing the entrepreneurial learning process. However, despite the rapid proliferation of EEP as the mainstream academic offering, previous literature argues that the current EEP delivery lacks the rigour and efficacy to provide a pedagogical experience that suits different personal identities that the students bring along into the classroom; thus, affecting their passion for entrepreneurship. In light of this, we review extensive literature related to entrepreneurial learning process, entrepreneurship education as well as the development of a passion for an activity. We also propose a theoretical framework of what may be missing in the current setup. We focus our discussion on the micro-foundation of the entrepreneurial learning process that occurs deep in the cognitive structure of individuals. Through the narrative literature review approach, we found that the lack of depth while the students validating their personal identity with the entrepreneurial learning activity affects the development of their passion for entrepreneurship. We offer refreshing insights into the importance of heuristic thinking, which embodies students’ personal identity, and its interplay with the pedagogical experience during the entrepreneurial learning process. This is crucial in the promotion of a strong sense of identification with the entrepreneurial-related activity and deep affinity towards entrepreneurship. By recognising this missing element and linkage, the students will feel that their unique signature strength is being more appreciated, thus triggering a more intense reaction towards the learning stimuli. This is because they feel the profound recognition of their worthiness in the social circle as well as stronger belief about the mutual benefit between entrepreneurship and their ongoing personal life quest; which consequently allows their entrepreneurial passion to be further developed. This paper contributes to the underpinning insight of how entrepreneurial passion is developed, the way it can influence the interest of learning entrepreneurship in EEP and encourage the students to become more passionate about entrepreneurship.